Cross-sectional changes of the distal carpal tunnel with simulated carpal bone rotation. Issue 14 (26th October 2022) - Jordan, David; Li, Zong-Ming
Abstract: This study simulated the cross-sectional changes in the distal carpal tunnel resulting from inward rotations of the hamate and trapezium. Rotations which decreased the carpal arch width, increased the carpal arch area. For example, simultaneous rotation of 5 degrees around the hamate and trapezium centroids decreased the carpal arch width by 1.69 ± 0.17 mm and increased the carpal arch area by 6.83 ± 0.68 mm 2 . Although the bone arch area decreased, decompression of the median nerve would likely occur due to the adjacent location of the nerve near the transverse carpal ligament.